O processo de socialização profissional de professores do ensino superior atuantes no curso de administração: trajetórias, saberes e identidades - Cunha, Marciano de Almeida (2011)
This research has been developed from the interest in understanding which knowledges university professors have, how they have been built and organized through the professional socialization process. The focus is on professors who teach at the Administration course once most of them do not notably have a pedagogic formation. In order to identify the twelve subjects of this research, we used the results from the teachers evaluation carried out by private university students. The subjects were chosen according to the extreme results aiming heterogeneity of profiles. Through the biographical narratives obtained, in depth of knowledge, in long semi-structured intensive interviews, it was possible to know the life history and the professional trajectory of this intentional sample of professors. The data were organized and analyzed according to categories that emerged from the conceptual table and that alluded to the professional socialization process (biographical and relational means) and to the pre-professional and professional knowledges built through this process. The theoretical methodological referential is constituted by studies by Dubar, Tardif, Dubet and considers that the professors knowledges are a social knowledge, built in a context of professional socialization, legitimated by a system of institutions and the history of a society, nevertheless, without disconnecting who the professors are, what they do, think and say. The data revealed the professors heterogeneity due to a possible porosity of the teaching field in the Administration education. Those professors demonstrated that they have knowledges of epistemological (non teaching trajectory) and pedagogical (teaching trajectory) nature that are organized and articulated by the processes of communication in the teaching activity